Pheno- and Genotyping of Hopanoid Production in Acidobacteria - Damsté, Jaap S. Sinninghe; Rijpstra, W. Irene C.; Dedysh, Svetlana N.; Foesel, Bärbel U.; Villanueva, Laura (Frontiers in Microbiology, 2017)
Hopanoids are pentacyclic triterpenoid lipids synthesized by different bacterial groups. Methylated hopanoids were believed to be exclusively synthesized by cyanobacteria and aerobic methanotrophs until the genes encoding for the methylation at the C-2 and C-3 position (hpnP and hpnR) were found to be widespread in the bacterial domain, invalidating their use as specific biomarkers. These genes have been detected in the genome of the Acidobacterium ‘Ca. Koribacter versatilis’, but our knowledge of the synthesis of hopanoids and the presence of genes of their biosynthetic pathway in other member of the Acidobacteria is limited. We analyzed 38 different strains of seven Acidobacteria subdivisions (SDs 1,3,4,6,8,10, and 23) for the presence of C30 hopenes and C30+ bacteriohopane polyols (BHPs) using the Rohmer reaction. BHPs and/or C30 hopenes were detected in all strains of SD1 and SD3 but not in SD4 (excepting Chloracidobacterium thermophilum),6,8,10 and 23. This is in good agreement with the presence of genes required for hopanoid biosynthesis in the 31 available whole genomes of cultivated Acidobacteria. All genomes encode the enzymes involved in the non-mevalonate pathway ultimately leading to farnesyl diphosphate but only SD1 and 3 Acidobacteria and C. thermophilum encode all three enzymes required for the synthesis of squalene, its cyclization (shc), and addition and modification of the extended side chain (hpnG, hpnH, hpnI, hpnJ, hpnO). In almost all strains, only tetrafunctionalized BHPs were detected; three strains contained variable relative abundances (up to 45%) of pentafunctionalized BHPs. Only ‘Ca. K. versatilis’ contained methylated hopanoids (i.e. 2,3-dimethyl bishomohopanol), although in low (<10%) amounts. These genes are not present in any other Acidobacterium, consistent with the absence of methylated BHPs in the other examined strains. These data are in agreement with the scattered occurrence of methylated BHPs in other bacterial phyla such as the Alpha-, Beta- and Gammaproteobacteria and the Cyanobacteria, limiting their biomarker potential. Metagenomes of Acidobacteria were also examined for the presence of genes required for hopanoid biosynthesis. The complete pathway for BHP biosynthesis was evident in SD2 Acidobacteria and a group phylogenetically related to SD1 and SD3, in line with the limited occurrence of BHPs in acidobacterial cultures.